2001
DOI: 10.1055/s-2001-12473
|View full text |Cite
|
Sign up to set email alerts
|

Farbkodierte Darstellung des Lungenparenchyms bei vermuteter Lungenembolie mittels Mehrschicht-Spiral-CT

Abstract: Summary. Purpose: The purpose of our preliminary study was to evaluate the feasibility of a new technique for the perfusion weighted color display of the density of lung parenchyma derived from multi-slice CT (MSCT) data sets of clinical routine examinations for visualization of pulmonary embolism (PE). Materials and Methods: Imaging of patients with suspected PE was performed on a commercially available MSCT (Somatom Volume Zoom; Siemens, Forchheim, Germany) after intravenous application of 120 cc of contrast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(5 citation statements)
references
References 10 publications
0
4
0
1
Order By: Relevance
“…Previous studies have evaluated CT for the assessment of lung perfusion in patients with suspected pulmonary embolism. In a study by Wildberger et al, perfusion weighted maps were generated by color-coding the density of lung parenchyma in contrast-enhanced CTA [6]. Schoepf et al evaluated a dynamic multisection EBCT protocol for pulmonary perfusion imaging [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have evaluated CT for the assessment of lung perfusion in patients with suspected pulmonary embolism. In a study by Wildberger et al, perfusion weighted maps were generated by color-coding the density of lung parenchyma in contrast-enhanced CTA [6]. Schoepf et al evaluated a dynamic multisection EBCT protocol for pulmonary perfusion imaging [7].…”
Section: Introductionmentioning
confidence: 99%
“…The idea of lung perfusion imaging by CT in PE is not new. In a previous study by Wildberger et al, density differences of the perfused and non-perfused lung on lung CTA data were highlighted by spectral color coding [6]. The main disadvantage of this approach is that differences in the density of lung parenchyma may also be caused by emphysema, air-trapping, and ground-glass opacities.…”
mentioning
confidence: 98%
“…Nevertheless, higher CT numbers could still inform on the level of functionality of an area due to an increased amount of contrast agent. In that regards, Wildberger et al have shown how perfused map based on the intensity of CT numbers could help detect pulmonary embolism. By combining this idea with the same thresholding step described in the DECT method, the functional level Fi is directly retrieved from the CT number of the voxels inside the functional area of the CT mixed images.…”
Section: Methodsmentioning
confidence: 99%
“…16,17 The DECT approach was also successful to detect perfusion defects in the context of pulmonary embolism [18][19][20][21][22] and parenchymal lung disease. 23,24 Other single-energy CT (SECT) techniques may also process contrast-enhanced CT images to produce functional maps of the lung parenchyma; 6,25,26 however, they do not quantitatively address the perfused blood volume.…”
Section: Introductionmentioning
confidence: 99%
“…Hierzu erschienen Computer-generierte Rekonstruktionen im Sinne einer multiplanaren Reformatierung (MPR) in der jeweils entsprechenden Orientierung hilfreich und einfach durchführbar [9,10]. Ziel dieser Mitteilung ist es, die Hilfestellung von multiplanaren Reformatierungen von 3 He-MRT und HR-CT beim Vergleich der beiden Verfahren anhand der Zuordnung anatomischer und pathologischer Strukturen zu prüfen.…”
Section: Introductionunclassified